a) AxB =Φ <====> [ (a,b)εAxB <-----> (a,b)εΦ] <=====>[(aεA & bεB)<------>(aεΦ & bεΦ)] <====>[(aεA----->aεΦ) & (bεB------>bεΦ)] ======>(aεA----->aεΦ)====> A= Φ ====> A=Φ v B=Φ.(adsbygoogle = window.adsbygoogle || []).push({});

**Physics Forums - The Fusion of Science and Community**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Is that proof correct?

Loading...

Similar Threads - proof correct | Date |
---|---|

I An easy proof of Gödel's first incompleteness theorem? | Mar 6, 2018 |

I Cantor's decimal proof that (0,1) is uncountable | Sep 27, 2017 |

A A "Proof Formula" for all maths or formal logic? | Apr 19, 2017 |

Is my proof correct? | Sep 12, 2011 |

Is that proof correct? | Apr 11, 2011 |

**Physics Forums - The Fusion of Science and Community**